An Empirical Investigation on International Journals of Tourism, Travel, Recreation and Leisure - Nazmi Kozak (Türk Kütüphaneciliği)
This study presents the results of an empirical research carried out amongst tourism, travel, recreation and leisure journals published, internationally. The findings of previous research were used for the development of the questionnaire instrument. The questionnaire was mailed to the Chief-Editors of 115 journals. A total of 33 usable questionnaires were returned yielding a 29 Chief-Editors of 115 journals. A total of 33 usable questionnaires were returned yielding a 29 percent response rate. SPSS for Macintosh was used for the analysis of data. Findings were analysed on the basis of three groups entitled 1general issues', 'review process of manuscripts' and 'publication of manuscripts'. The study revealed that the journals were in an attempt to be consistent with the manuscript review and publication guidelines recognised in the international academia.